Metodología de evaluación de sensibilidad, selectividad y velocidad usando simulación en tiempo real de un caso de estudio de 8 nodos (2020)
This document presents a selectivity, sensibility, and speed study of a protection system with 14 directional overcurrent relays (Function 67) associated to an interconnected power system of 8 nodes and 7 lines of transmission in 150 [kV] that has been implemented in a soft real-time simulation platform called Typhoon [1-2]. Results have been contrasted with those one obtained by the classification methodology of directional relays trip sequences proposed by De Oliveira and Sorrentino [3-5]. As a result, it is obtained that 93% of trip sequence cases found with simulation, matches with those one observed by [3]. Those differences are explained by the fact that the real-time platform is more accurate than that one proposed in [3], considering key aspects as three-phase power system modeling, short circuit asymmetric current, and virtual relays time operations.